Monitoring strategies in children with asthma: a randomised controlled trial. Issue 6 (30th March 2015) - Voorend-van Bergen, Sandra; Vaessen-Verberne, Anja A; Brackel, Hein J; Landstra, Anneke M; van den Berg, Norbert J; Hop, Wim C; de Jongste, Johan C; Merkus, Peter J; Pijnenburg, Mariëlle W
Abstract : Background: Asthma guidelines recommend monitoring of asthma control. However, in a substantial proportion of children, asthma is poorly controlled and the best monitoring strategy is not known. Objectives: We studied two monitoring strategies for their ability to improve asthma outcomes in comparison with standard care (SC): web-based monthly monitoring with the (Childhood) Asthma Control Test (ACT or C-ACT) and 4-monthly monitoring of FENO . Methods: In this randomised controlled, partly blinded, parallel group multicentre trial with a 1-year follow-up, children aged 4–18 years with a doctor's diagnosis of asthma treated in seven hospitals were randomised to one of the three groups. In the web group, treatment was adapted according to ACT obtained via a website at 1-month intervals; in the FENO group according to ACT and FENO, and in the SC group according to the ACT at 4-monthly visits. The primary endpoint was the change from baseline in the proportion of symptom-free days (SFD). Results: Two-hundred and eighty children (mean age 10.4 years, 66% boys) were included; 268 completed the study. Mean changes from baseline in SFD were similar between the groups: −2.1% (web group, n=90), +8.9% (FENO group, n=91) versus 0.15% (SC, n=87), p=0.15 and p=0.78. Daily dose of inhaled corticosteroids (ICS) decreased more in the web-based group compared with both other groups (−200 μg/day, p<0.01), while ACT and SFD remained similar. Conclusions: The change from baseline in SFD did not differ between monitoring strategies. With web-based ACT monitoring, ICS could be reduced substantially while control was maintained. Trial registration number: NTR 1995.